2019
DOI: 10.1182/blood-2019-131056
|View full text |Cite
|
Sign up to set email alerts
|

A Bcma and CD19 Bispecific CAR-T for Relapsed and Refractory Multiple Myeloma

Abstract: Introduction Chimeric Antigen Receptor T cells (CAR-T) therapy, e.g. B Cell Maturation Antigen (BCMA)-directed CAR-T has provided an encouraging modality for relapsed and refractory management of multiple myeloma (MM). However, a significant portion of patients still relapse with progressive disease after monospecific anti-BCMA CAR-T treatment. It has been demonstrated that CD19-directed CAR-T was effective in certain MM patients, likely due to CD19 expression on subsets of MM cells, and/or unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…A BCMA-CD19 bispecific CAR-T product was recently manufactured in China. It was constructed by linking BCMA and CD19 scFv, joined by a CD8 hinge, transmembrane domain, co-stimulatory domain, and CD3ζ [154]. In preclinical study, BCMA-CD19 CAR-T cells were shown to be highly effective in eliminating MM tumor cells both in vitro and in vivo and appeared more cytotoxic than single CAR-T. A first-in-human trial has been initiated.…”
Section: Cd19/bcma Bispecific Car-t Cellsmentioning
confidence: 99%
“…A BCMA-CD19 bispecific CAR-T product was recently manufactured in China. It was constructed by linking BCMA and CD19 scFv, joined by a CD8 hinge, transmembrane domain, co-stimulatory domain, and CD3ζ [154]. In preclinical study, BCMA-CD19 CAR-T cells were shown to be highly effective in eliminating MM tumor cells both in vitro and in vivo and appeared more cytotoxic than single CAR-T. A first-in-human trial has been initiated.…”
Section: Cd19/bcma Bispecific Car-t Cellsmentioning
confidence: 99%
“…Biclonal constructs (anti-CD19 and BCMA) were tested in phase 1 study. All 5 patients that received it responded with no significant side effects (mild CRS was seen in 2 cases, no ICANS was observed) [18].…”
Section: Biclonal Cartmentioning
confidence: 95%
“…The APRIL-based CAR T-cell product is currently investigated in the AUTO2 trial (NCT03287804) ( 133 ). As mentioned previously, other multispecific CAR T-cell products containing a bicistronic BCMA and SLAMF7-directed CAR ( 176 , 177 ) or simultaneously manufactured BCMA- and GPRC5D-directed CAR T-cells ( 121 ) have been investigated preclinically, and clinical testing of bispecific CAR T-cells targeting BCMA and CD38 ( 132 ) or BCMA and CD19 ( 178 ) are ongoing in China. Even if preliminary data of treatment with bispecific CAR T-cells has been encouraging, the comparison of bispecific and single-antigen specific CAR T-cells needs to be performed in randomized clinical trials ( 132 ).…”
Section: Tumor Directed Strategies To Reduce Antigen Lossmentioning
confidence: 99%